2009
DOI: 10.2147/ijgm.s5907
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory recorded ST segment depression on ECG is associated with lower cognitive function in healthy elderly men

Abstract: ST segment depression (STDE) has been found to be associated with cardiovascular disease in the elderly. Studies of the relation of ambulatory STDE to cognitive function in elderly persons aged 80 years or above is lacking.Objective:To study the association between STDE and cognition.Design and participants:A cross-sectional cohort study of 88 81-year-old men from the population study “Men born in 1914” investigated in an outpatient research clinic. Measurements included ambulatory 24-hour electrocardiogram (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Furthermore, large LVIDd has been reported as an independent predictor for all-cause mortality or hospitalization for cardiac causes [32]. We have in an earlier study found that ambulatory ST segment depression, as a measure of ischemic heart disease (IHD), was associated with lower cognitive function, both visuospatial and verbal [14]. In our material, 144 subjects (68%), had a normal LVIDd, whereas 57 (27%) had enlarged.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Furthermore, large LVIDd has been reported as an independent predictor for all-cause mortality or hospitalization for cardiac causes [32]. We have in an earlier study found that ambulatory ST segment depression, as a measure of ischemic heart disease (IHD), was associated with lower cognitive function, both visuospatial and verbal [14]. In our material, 144 subjects (68%), had a normal LVIDd, whereas 57 (27%) had enlarged.…”
Section: Discussionmentioning
confidence: 59%
“…The following year, at age 82–83, 72 survivors underwent CBF measurements. Background data were published previously [13,14]. Information on background factors was taken from the examination at the age of 68 years.…”
Section: Methodsmentioning
confidence: 99%